Study of risk factors associated with ectopic pregnancy: an observational study - Uthpala, V.; Gracelyn, J. Leila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Any pregnancy in which the fertilised ovum implants outside the intrauterine cavity is an ectopic pregnancy. Since none of the extrauterine areas can support placental attachment or a developing embryo, it invariably risks rupture and haemorrhage. It is thus considered a life-threatening emergency. Lower abdominal pain with vaginal bleeding in women of reproductive age raises the suspicion of an ectopic pregnancy. However, this is not always the case; some may present vague symptoms, oblivious to the underlying pathology. Hence this study aimed to document the potential risk factors for ectopic pregnancy. Methods: This prospective study was carried out at a tertiary care hospital and included 60 women diagnosed with ectopic pregnancy. Detailed history, menstrual and obstetric history, clinical examination, urine pregnancy test, and ultrasonography were obtained for each patient. Their clinical profile was noted, including their name, age, marital status, socioeconomic status, parity, and last childbirth. A list of potential risk factors was compiled. The general, systemic, abdominal and vaginal examination was done. Data were collected and evaluated. Results: 60 cases of ectopic pregnancies were diagnosed during the study period. The highest number of patients were noted in the 20-24 years age group (n=21) and the least in the 35–39 years age group (n=1). Pain in the abdomen was the most commonly noted symptom at 88.3%, followed by bleeding per vaginum (76.7%), vomiting (73.3%), fainting (58.3%), shock (30.0%), and abdominal distention (21.7%). While 18.3% of cohorts did not present with any risk factor, pelvic inflammatory disease (n=13) was the most commonly noted risk factor. Conclusions: Ectopic pregnancy is a life-threatening medical emergency which requires a keen eye for detail. A comprehensive narrative of clinical history, signs and symptoms aided by appropriate diagnostic tools will help side-step fatalities.